Tikhii chas . Tikhii chas . Rest Time . Тихий час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the TV-anchor Vladislav Listiev; segment on tattoo fashions in Russia, pencil collectors and the "Sportloto" lottery. Featured in the program: List'ev, Vladislav Nikolaevich (Anchor) Contributors: Sychev, Andrei (Anchor) Интервью с телеведущим Владиславом Листьевым; сюжеты о моде на татуировки в России,, о коллекционерах карандашей и о лотерее "Спортлото.". В программе участвуют: Листьев, Владислав Николаевич (Телеведущий) Создатели: Сычев, Андрей (Ведущий/Ведущая)